2013
DOI: 10.1109/tap.2013.2242033
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Equivalent Circuit Models to Elucidate Power Balance in Scattering Problems

Abstract: Analytical and equivalent circuit models are presented to elucidate the balance of powers in scattering processes. Specifically, closed-form expressions of the associated maximal extracted, scattered, absorbed and reactive powers are formulated. The circuit model then helps to characterize in a straightforward manner these powers, to provide physical insights into the inter-relationships among this set, and thus guides the resolution of their fundamental limits. The analysis demonstrates that the absorbed powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 20 publications
(36 reference statements)
3
55
0
Order By: Relevance
“…They also provide a means to investigate the associated balance of powers and the fundamental limits on each contribution. This work therefore completes previous studies based on 3D geometries [3,21,22]. Specifically, we have presented upper bounds of the absorbed, scattered and extracted power for 2D geometries, thus revealing the main similarities and differences between the 2D and 3D scenarios, as well as the difficulties of analyzing 3D objects with high aspect ratio by using a vector spherical harmonic decomposition.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…They also provide a means to investigate the associated balance of powers and the fundamental limits on each contribution. This work therefore completes previous studies based on 3D geometries [3,21,22]. Specifically, we have presented upper bounds of the absorbed, scattered and extracted power for 2D geometries, thus revealing the main similarities and differences between the 2D and 3D scenarios, as well as the difficulties of analyzing 3D objects with high aspect ratio by using a vector spherical harmonic decomposition.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, one finds from (37) that the upper bound of absorbed power for 2D objects increases as 2N + 1 along with the number of harmonics N , while it was found to increase as N 2 + 2N for 3D geometries [22]. Thus, it can be concluded that the growth rate per harmonic is much smaller in 2D geometries.…”
Section: T Z≶ Nmentioning
confidence: 92%
See 3 more Smart Citations